2023
DOI: 10.1021/acscatal.3c00353
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable Redox Noninnocent Bathocuproine-Iron Complex for Cycloaddition Reactions

Abstract: In this work, we aim to formally design iron(0) complexes combined with a phenanthroline-type ligand (phen) and investigate their utility in cycloaddition catalysis. Owing to the strong noninnocence of the phen scaffold, its ligation to reduced iron oxidation states classically affords particularly unstable species. The reported examples of such well-defined coordination complexes are thus particularly scarce. We demonstrate herein that a strategic steric protection of the C4 and C7 positions of the phen ring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Note that in the absence of TEOA, the system with Fe II ( MeHp )Cl 2 did not induce CO 2 reduction. This indicates that a singly reduced Fe II ( MeHp )Cl 2 , in which the added electron was localized on the MeHp ligands, i.e., Fe II ( MeHp •– )Cl 2 , could not induce CO 2 reduction. Thus, the production of MeHp H • and its interaction with the Fe ion are essential for the CO 2 reduction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Note that in the absence of TEOA, the system with Fe II ( MeHp )Cl 2 did not induce CO 2 reduction. This indicates that a singly reduced Fe II ( MeHp )Cl 2 , in which the added electron was localized on the MeHp ligands, i.e., Fe II ( MeHp •– )Cl 2 , could not induce CO 2 reduction. Thus, the production of MeHp H • and its interaction with the Fe ion are essential for the CO 2 reduction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Spectroscopic data matched with literature. [34] Typical procedure for cycloadditions A 10 mL round bottom two-necked flask was charged with (L 1 )FeCl 2 (29.2 mg, 0.06 mmol, 1.00 equiv.) and bathocuproine (L 1 ), 22.6 mg, 0.06 mmol, 1.00 equiv.).…”
Section: Discussionmentioning
confidence: 99%
“…We reported that (L 1 ) 2 Fe was an efficient alkyne [2 + 2 + 2] cycloaddition catalyst, albeit under thorough air-sensitive, glovebox conditions. [34] Because (L 1 )FeCl 2 is readily obtained in a single, quantitative step from commercially available ligand L 1 and can subsequently be stored with no need of specific air-sensitive procedures, it appears to be a particularly appealing catalyst for synthetic purposes, because the targeted transformations are carried out with no need of glovebox or drastic air-and moisture-free conditions. In this report, we demonstrate that cycloadditions mediated by in situ generated (L 1 ) 2 Fe can be achieved in such user-friendly conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations